Kajian Yuridis Terkait Penentuan Besar Upah Pekerja Berdasarkan Pasal 88 C Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Ida Bagus Gede Wiswamitra; I Nyoman Putu Budiartha; I Wayan Kartika Jaya Utama (Jurnal Analogi Hukum, 2022)
The problem of manpower or labors is an typicals problems that we headr for develop country, included Indonesia. One of those problems is terminations of employment by the company. Based on the descriptions of the text above, author can formulates two problems that will be discuss in this paper. The problems formulations at this research are: How the Wage System in Law Number 11 of 2020 concerned occupation Creations? And how determination of the workers' wages based on Article 88 C of Law Number 11 of 2020 concerning Job Creation? The types of researches used is normative legal research, that are legal research conducted by researching library materials. The conclusion in this study is that the Government changed the wage provisions in Law No. 11 of 2020 concerning Job Creation. These changes include the abolition of the district/city minimums wage (UMK) and the sector-based minimum wage in the province or district/city. The Employment Creation Act changes the policy regarding the wages of workers which was previously regulated by the Manpower Act.